SOSOK LAKI-LAKI DALAM IKLAN MS GLOW FOR MEN “SEMUA JUGA BISA” - Fillmore Galih Wibisana, Kuirinus; Hasfi, Nurul; Lukmantoro, Triyono (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Male facial care advertisement has the aim of offering products as a solution to men's facial problems through the talent presented as the image of the product. Current facial care advertisements feature a metrosexual figure, but researchers found a different figure through the MS Glow For Men